Fluoroscopy time and scattered radiation during electrophysiology procedures: analysis of one-year data of a laboratory providing electrophysiology training. Issue 3 (4th May 2021) - Gulsen, Kamil; Akgun, Taylan; Kup, Ayhan; Uslu, Abdulkadir; Kanar, Batur Gonenc; Taylan, Gokay; Kayan, Fethullah; Barutcu, Suleyman; Kepez, Alper; Demir, Serdar
Abstract: Objectives: Patients and medical staff expose to significant radiation during electro-physiological (EP) procedures. There are few data regarding the leading factors of longer fluoroscopy time and higher scattered radiation in a laboratory giving EP training during those interventions. Material and methods: The patients' recordings that underwent EP procedure in a single centre arrhythmia unit from February 2019 to January 2020 were examined. Prospectively collected data regarding procedure duration, fluoroscopy time and total air kerma, demographic characteristics of the patients, type of procedure, success of ablation and the use of electro anatomic mapping were retrospectively evaluated. Predictors of total air kerma were analysed with linear regression analysis. Results: Study population consisted of 437 patients with a median age of 47 (39–56); 184 (42.1%) were male. Median fluoroscopy time was 768 (420–1320) seconds and median cumulative air kerma was 369 (191–750) mGy. Fluoroscopy time and cumulative air kerma were significantly lower in diagnostic EP studies compared to other procedures. There was no difference in terms of total air kerma between the procedures other than the diagnostic EP study. In multivariable linear regression analysis; body surface area, fluoroscopy time, not using the electro-anatomical mapping, unsuccessful ablation and atrial flutter ablation were predictors of total air kerma in EP studies performed by trainees. Conclusion: Scattered radiation during EP procedures performed by in-training operators is related with some factors. Awareness about those may help to effort reducing the harmful effect of ionising radiation.